2022
DOI: 10.3389/fmed.2022.879861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of First Trough Vancomycin Concentration on the Occurrence of AKI in Critically Ill Patients: A Retrospective Study of the MIMIC-IV Database

Abstract: BackgroundVancomycin can effectively inhibit Gram-positive cocci and is widely used in critically ill patients. This study utilized a large public database to explore the effect of patients' first vancomycin trough concentration (FVTC) on the occurrence of acute kidney injury (AKI) and mortality after receiving vancomycin treatment in intensive care unit (ICU).MethodsCritically ill patients who used vancomycin in the Medical Information Mart for Intensive Care (MIMIC) IV have been retrospectively studied. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this regard, it is necessary for clinicians to deepen their understanding of the importance of VAN concentration monitoring. A retrospective study showed that VAN nephrotoxicity was associated with trough concentration levels, with the risk of AKI being 1.36 and 1.76 times higher in patients with trough concentrations between 15–20 mg/L and > 20 mg/L than in the control group (< 10 mg/L) [ 27 ]. Based on statistical trough concentration data, we simulated an ROC curve, and according to the Youden index, the trough concentration of VAN should not exceed 15.845 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is necessary for clinicians to deepen their understanding of the importance of VAN concentration monitoring. A retrospective study showed that VAN nephrotoxicity was associated with trough concentration levels, with the risk of AKI being 1.36 and 1.76 times higher in patients with trough concentrations between 15–20 mg/L and > 20 mg/L than in the control group (< 10 mg/L) [ 27 ]. Based on statistical trough concentration data, we simulated an ROC curve, and according to the Youden index, the trough concentration of VAN should not exceed 15.845 mg/L.…”
Section: Discussionmentioning
confidence: 99%